Motivators and barriers for physical activity among health-care professionals: A qualitative study - Leyanna Susan George; Harsha Lais; Maya Chacko; Charutha Retnakumar; Vijayakumar Krishnapillai (Wolters Kluwer Medknow Publications, 2021)
Background: Physical inactivity is one of the critical risk factors for lifestyle-related diseases. In Kerala, the life expectancy of doctors who are considered the gatekeepers of health was found to be 13 years lower than the general population. Objective: The objective was to identify the motivators and barriers for physical activity among doctors and nurses belonging to public and private health-care sectors in Ernakulam district. Methodology: Qualitative study was conducted using a grounded theory approach. A total of 30 in-depth interviews and 8 focus group discussions were conducted among doctors and nurses, respectively. The audio-recorded data were transcribed, coded, and thematically analyzed. Results: The main themes identified were motivators, barriers, and future considerations for physical activity. The factors motivating doctors were the fear of noncommunicable diseases and to stay fit, while the nurses were more concerned about their body image. The common barriers were gender, lack of time, laziness, bad climate, and safety issues. Overreliance on medication and prioritizing their patients' health over their own were additional barriers. Conclusion: Physical activity among doctors and nurses is severely compromised. Provision of a favorable environment and behavior change is needed to combat the silent epidemic of physical inactivity.